The Effectiveness of Using Cooperative Integrated Reading and Composition Learning Method Towards Students’ Reading Comprehension in Narrative Text - Rahma, Shafira Alifya; Delfi, Syofia; Masyhur, Masyhur (CV. Rayyan Dwi Bharata, 2024)
This study aims to find out the effectiveness of using Cooperative Integrated Reading and Composition learning method towards students’ reading comprehension in narrative text. In conducting this study, the writer applied pre-experimental method and one group pre-test and post-test design. This study is conducted to the first-grade students of SMAN 15 Pekanbaru. The purposive sampling is the type of sampling technique in this study where 35 students from class X B as the experimental class. The instrument used to collect the data was a multiple-choice test that consisted of 40 questions. Then the data obtained from pre-test and post-test were analyzed by SPSS version 25.0. The hypothesis was conducted using Paired Sample Test. The results of the data analysis showed T-test was higher than T-table (24.911 2.022) with a significant level of 5% which means the altenative hypothesis of this study (Ha) is accepted. Therefore, CIRC learning method affects students’ reading comprehension in narrative text. It is suggested to use CIRC learning method for teacher, students, and researcher. CIRC learning method can encourage students to improve their ability in reading comprehension especially in narrative text.